Adapting to change: Visitor patterns in national parks across the pandemic timeline - Dehui Christina Geng; Mingze Chen; Harry Seely; Howie W. Harshaw; Christopher Gaston; Wanli Wu; Guangyu Wang (Trees, Forests and People)
The COVID-19 pandemic has substantially impacted visitor behaviour and forest tourism management, introducing new visitor patterns that persist in the post-COVID-19 period. As critical components of national parks, forests and tree-dominated natural environments have gained renewed attention for their role in promoting mental and physical health during public health crises. This study analysed pandemic-induced shifts in visitor activity and movement patterns from a temporal-spatial perspective in Banff, Jasper, Yoho and Kootenay National Parks using social media big data from pre, peri, and post COVID-19. Temporal analysis of social media posts aligned with official park attendance trends (2019–2023), validating big data as a reliable indicator. Results show a long-term behaviour shift toward nature-immersive activities in remote and forested wilderness areas, reduced traffics on historically popular routes, and emerging between-park connectivity. Seasonal and spatial visitation patterns became less centralised, increasing conservation pressures in ecologically sensitive forested areas and necessitating proactive infrastructure, zoning, and transit management. This research fills the knowledge gap on pandemic-driven visitation trends using big data, offering the implications extend beyond the current pandemic for effective and prompt park resources and tourism management, balancing conservation and public well-being.